Patient-Oriented Digital Health Intervention for Chronic Kidney Disease: From Evidence to Everyday Care - Maoliosa Donald; Dwight Sparkes; Matthew Thomas James (Journal of Medical Internet Research, 2026)
Abstract Lightfoot and colleagues explored patient perspectives on the implementation and sustainability of My Kidneys & Me, a digital self-management intervention for chronic kidney disease, identifying key factors that may influence successful adoption into routine care. The study shows that generating evidence of effectiveness alone is insufficient for successful mobilization into practice, highlighting the importance of embedding implementation evaluation in concert with clinical trials to identify practical strategies that support real-world uptake and sustained use.